Análise de manifestações patológicas na escola estadual Alvani de Freitas dias na cidade de Apodi-RN: diagnóstico e medidas corretivas. - Gama, Karine Persia de Lima (Universidade Federal Rural do Semi-Árido, 2019)
Buildings have a lifetime, but there are factors that can prolong or delay this time. The success in the design and execution of the project, together with the quality of the materials and labor, are aspects that contribute favorably in the preservation of the construction. On the other hand, pathological manifestations delay these time, which in addition to affecting its structure require the financial resources to carry out the indicated treatments. This research seeks to contribute to the identification and decision-making for the recovery of the pathological manifestations found at the Alvani de Freitas Dias State School in the city of Apodi-RN, seeking to ascertain the possible causes, diagnosis and treatment. The methodology used in the study consisted of an on-site visit to detect the existing pathologies and their motivation, indicating the order of prioritization for recovery according to the GUT method (gravity, urgency and tendency) and damage recovery techniques . Finally, it could be verified that 61% of the pathologies found are related to the corrosion of reinforcement in concrete, having as the major causative agents the humidity, poor quality of the concrete and insufficient covering of the structure. It was still possible to perceive that the absence of maintenance is the main cause of the pathological manifestations observed in the building, this factor explains the seriousness of the problems that occur in the building.
Monografia
Keywords: Edificação; Vida útil; Patologias; Manutenção; Tratamento; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA